2020
DOI: 10.1093/bjsw/bcaa129
|View full text |Cite
|
Sign up to set email alerts
|

‘This is Still All about Love’: Practitioners’ Perspectives of Working with Family Carers Affected by the Harmful Behaviour of the Older Person for Whom They Care

Abstract: This article explores a hidden and under-acknowledged dimension of caring in family life: when older people with care needs act in a harmful, abusive or violent way towards the family member(s) who cares for them. Thirty-eight health and social care professionals, working in the UK, took part in five focus groups to explore their experience of working with families in this situation. The group discussions were stimulated by vignettes developed from interviews with carers affected by harmful behaviour, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 39 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…The vignette scenario can be generated in different ways. It can be based on literature (Schoenberg and Ravdal, 2000), interviews with people with lived experience (Pwle) (Isham et al, 2021; Roets et al, 2016) or professionals (Bradbury-Jones et al, 2014), analysis of case records (Engwall et al, 2019; Kristensen, 2011; Stevens et al, 2010) or serious case reviews (Wilkins, 2015), media reported incidents (Aujla, 2020), practice knowledge (Bain, 2008) or a combination of these. Zeijlmans et al (2019: 402), for example, observed professionals in two organisations and analysed case files from a third organisation.…”
Section: Designing a Text-based Vignettementioning
confidence: 99%
See 3 more Smart Citations
“…The vignette scenario can be generated in different ways. It can be based on literature (Schoenberg and Ravdal, 2000), interviews with people with lived experience (Pwle) (Isham et al, 2021; Roets et al, 2016) or professionals (Bradbury-Jones et al, 2014), analysis of case records (Engwall et al, 2019; Kristensen, 2011; Stevens et al, 2010) or serious case reviews (Wilkins, 2015), media reported incidents (Aujla, 2020), practice knowledge (Bain, 2008) or a combination of these. Zeijlmans et al (2019: 402), for example, observed professionals in two organisations and analysed case files from a third organisation.…”
Section: Designing a Text-based Vignettementioning
confidence: 99%
“…Responses to vignettes give insights into people’s norms and beliefs whilst taking into account contextual factors (Grootegoed and Smith, 2018). Vignettes allow an insight into social work practice, decision-making and service user experiences without the need for examples from social workers’ practice that would potentially include sensitive data or breach confidentiality (Isham et al, 2021: 3196). Vignettes can be used to address sensitive topics that are otherwise difficult to talk about (Grootegoed and Smith, 2018; Wilks, 2004).…”
Section: Benefits and Limitations Of Vignettesmentioning
confidence: 99%
See 2 more Smart Citations
“…Older women report that feelings of shame and anticipatory stigma inhibit them from disclosing sexual and IPV particularly when carried out by a life-long partner or family member [20]. The complex dynamics of love, care and inter-dependency in older age create additional challenges for older women seeking help in relation to a taboo expression of violence and abuse-that perpetrated by people who need and who 'give' care [21,22]. Help-seeking is further hampered by a lack of specialist, age-sensitive services in most countries.…”
Section: Disclosure and Help-seeking: Formal And Informal Routesmentioning
confidence: 99%